Strategi Pemasaran dan Inovasi Produk dalam Keberlanjutan Bisnis: Studi Kasus UMKM di Masa Pandemi - Aghisyna Dwi Inayah Fikamalina; Dhea Fitri Puspitayani; Devira Elsa Mei Shella; Rusdi Hidayat Nugroho; Maharani Ikaningtyas (ManBiz: Journal of Management and Business, 2024)
Marketing and innovation strategies are the key to success inining a business, success determined by victory in the face of competition using established strategies to innovate with their business. Innovation in UMKM can be seen through three dimensions: process innovation, product innovation, and management system innovation. In this case product innovation becomes the most important part to improve UMKM performance. In its implementation, paying attention to the ideal time and how to innovate is an important thing when the entrepreneur will implement the necessary marketing strategy. Marketing startups and product innovations are the key to success inining a business, success is determined by victory in the face of competition using established strategies to innovate with the business. In the implementation of marketing strategies as well as product innovation should pay attention to the ideal time and how things innovate is important when the entrepreneur will implement the necessary marketing strategy.